FACTORS AFFECTING DISTRIBUTION AND DETECTION OF BOREAL CHORUS FROGS (Pseudacris maculata) AND WOOD FROGS (Rana sylvatica) AT CAPE CHURCHILL, MANITOBA - Mannan, Nicholas R; Perry, Gad; Andersen, David E; Boal, Clint W (2006)
Amphibian populations are declining globally (Jennings and Hayes 1985, Beebee et al. 1990, Blaustein and Wake 1990). Disease, introduced predators, ultraviolet radiation, pollution, environmental change, and habitat loss and degradation have been suggested factors responsible for amphibian population declines (Jennings and Hayes 1985, Beebee et al. 1990, Laurance et al. 1996, Pounds et al. 2006). However, the relative importance of each potential factor is often unknown in specific cases. Because the processes that underlie amphibian declines are not well understood, collaborative efforts, such as the North American Amphibian Monitoring Program (NAAMP), have been developed to collect basic ecological data, and to systematically monitor amphibian population trends. Despite efforts such as the NAAMP, there are still many areas where amphibian surveys have not been conducted and little is known about local populations.